United Against Rabies Forum: The One Health Concept at Work - Rachel Tidman; SM Thumbi; SM Thumbi; SM Thumbi; Ryan Wallace; Katinka de Balogh; Vivian Iwar; Isabelle Dieuzy-Labaye; Junxia Song; Sean Shadomy; Sean Shadomy; Yu Qiu; et al. (Frontiers Media S.A., 2022)
Human deaths from rabies are preventable and can be eliminated by applying a systematic One Health approach. However, this ancient disease still threatens the lives of millions of people in up to 150 countries and kills an estimated 59, 000 people every year. Rabies today is largely a disease of poverty, almost always linked to dog bites, with most deaths occurring in neglected communities in Africa and Asia. The disease places an immense economic burden on its victims, a cost that far outweighs the investment needed to control it. A global framework for rabies elimination in humans is set out in Zero by 30: The Global Strategic Plan to end human deaths from dog-mediated rabies by 2030. Despite the existence of proven control strategies and agreement on the path to eliminating human rabies deaths, mortality numbers from rabies remain high, and COVID-19 has set back efforts even further. But COVID-19 has also highlighted the value of a One Health approach to zoonotic disease and pandemic prevention. Rabies control programs offer a practical route to building One Health capacities that can also address other zoonotic threats, including those with pandemic potential. The United Against Rabies Forum aims to accelerate progress on rabies elimination while applying a One Health approach. The Forum promotes cross-sector collaboration among stakeholders and supports countries in their rabies elimination efforts. Increased political engagement and resource mobilization, both internationally and nationally, will be needed to achieve global rabies goals and can also make One Health implementation a reality.